On the various-heating-rates method for evaluating the activation energies of thermoluminescence peaks. (January 2022) - Chen, R.; Lawless, J.L.; Pagonis, V.
Abstract: The well-known various-heating-rates (VHR) method for evaluating the activation energy of thermoluminescence (TL) peaks is revisited. The method hinges on the shift of the TL peak with changing heating rate, and is based on the properties of first-order curves. Several works have shown that the same method yields a good approximation of the activation energy when general-order peaks are involved. A recent work by Maghrabi has presented a heuristic explicit expression for the magnitude of the shift between two heating rates within the first-order kinetics framework. In the present work, we address two related points. We show how the expression suggested by Maghrabi can be reached by making a very reasonable approximation of the original equation yielding the maximum condition. We also present an alternative expression which yields the amount of shift of the TL maximum with changing heating rate and with less approximation. The other point dealt with involves the results of a numerical study of the evaluation of the activation energy by the use of various heating rates in the more general one-trap-one-recombination-center (OTOR) situation. The results show that even in this general case, the various heating rates method yields very good results. The same is true for the "mixed-order" kinetics. The numerical results are accompanied by an analytical account which shows that the method yields very accurate activation energies in the rather general OTOR situation. Highlights: The various heating rates method for evaluating TL activation energy is revisited. The method is shown to be useful for non-first-order cases including OTOR. Numerical results and analytical account show the accuracy of the method. An expression for the size of shift of the peak with heating rate is proven.